Use of Simulation and Gaming to Enhance Entrepreneurship - Bagdonas, E.; Patašienė, I.; Patašius, M.; Skvernys, V. (Elektronika ir Elektrotechnika, 2010)
Business Game (BG) “Kietas riesutas” (“Hard Nut”) has already used for about ten years for teaching business basics. The study performed in 2007 has revealed insufficient attention given to entrepreneurship of engineering students. Thus it has been decided to propose the distance education module “Simulation of business processes” using BG. That could be expected to improve the module’s appeal and to encourage the students not just to learn the business basics, but also to deepen their understanding of business processes. The architecture of the described BG enables the use of additional extensions and gives the student an opportunity to learn not just about business, but about informatics as well. The compatibility between BG and Altman model has been checked and improvements to BG suggested.